LIKE, COMMENT AND SHARE: THE INTERPLAY OF SOCIAL MEDIA MARKETING, BRAND GESTALT AND BRAND PERSONALITY - Rayo, Edwina Fabiola; Rayo, Natashia Merrylien; Mandagi, Deske W. (Proceeding National Conference Business, Management, and Accounting (NCBMA), 2024)
Although there is a lot of research that discusses social media marketing, there is still not much that discusses the relationship between social media marketing and brand personality, especially not yet found research on social media marketing and brand personality involving brand gestalt variables. Therefore, this study aims to analyze the influence of social media marketing (SMM) on brand personality with brand gestalt as mediating variable on Starbucks Indonesia customers. This study used a quantitative descriptive method using primary data obtained from 232 respondents of Starbucks Indonesia customers within 3 months. The data analysis process uses the Structural Equation Model (SEM) which is carried out through the SmartPLS statistical program. The results of the study show that SMM does not have a direct positive and significant impact on brand personality but has a positive and significant impact on brand gestalt dimensions and their gestalt dimensions also have a positive and significant impact on brand personality. Furthermore, brand gestalt dimension fully mediates the effect of SMM on brand personality. This research provides additional literacy on SMM, brand personality and brand gestalt and provides information to practitioners in using SMM and brand gestalt in forming their brand personality.